1997
DOI: 10.1073/pnas.94.10.5267
|View full text |Cite
|
Sign up to set email alerts
|

A nontoxic mutant of cholera toxin elicits Th2-type responses for enhanced mucosal immunity

Abstract: We have characterized a nontoxic mutant of cholera toxin (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
280
5

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 290 publications
(292 citation statements)
references
References 37 publications
7
280
5
Order By: Relevance
“…Our results show robust expression of IFN-g, IL-2 and TNF-a in CD4 1 T cells after immunization with HEL and CT, whereas IL-4 and IL-5 were not detectable, which is in contrast with previous reports that indicated a Th2 cytokine response after ear immunization [10,11]; this also argues against the occurrence of dominant Th2 responses toward antigens that are coadministered with CT in mucosae [16,17]. In the skin, both Th1 and Th2 cytokines have been reported following immunization with OVA and CT [24].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results show robust expression of IFN-g, IL-2 and TNF-a in CD4 1 T cells after immunization with HEL and CT, whereas IL-4 and IL-5 were not detectable, which is in contrast with previous reports that indicated a Th2 cytokine response after ear immunization [10,11]; this also argues against the occurrence of dominant Th2 responses toward antigens that are coadministered with CT in mucosae [16,17]. In the skin, both Th1 and Th2 cytokines have been reported following immunization with OVA and CT [24].…”
Section: Discussioncontrasting
confidence: 99%
“…It has been reported that LCs remain in the epidermis for 48 h, even in the presence of Th1-polarizing adjuvants [7]. In our experiments, 24 h after CT or CTB inoculation in the ear, the number of LCs in the epidermis was reduced, suggesting that LCs could be mobilized from the dermis at this time point in the presence of strong adjuvants such as CT.Our results show robust expression of IFN-g, IL-2 and TNF-a in CD4 1 T cells after immunization with HEL and CT, whereas IL-4 and IL-5 were not detectable, which is in contrast with previous reports that indicated a Th2 cytokine response after ear immunization [10,11]; this also argues against the occurrence of dominant Th2 responses toward antigens that are coadministered with CT in mucosae [16,17]. In the skin, both Th1 and Th2 cytokines have been reported following immunization with OVA and CT [24].…”
contrasting
confidence: 89%
See 1 more Smart Citation
“…An alternative approach to circumvent this problem is the use of genetically detoxified heat labile enterotoxins of E. coli LTK63 or non-toxic mutant cholera toxin CT S61F. 125,134,135 The challenge currently faced by several laboratories is to discover whether or not the promising results obtained in the animal model can be reproduced in humans.…”
Section: Vaccination Development For Clinical Use and Future Of The Hmentioning
confidence: 99%
“…137 Additionally, the use of non-toxic LTK63 or CT S61F for oral vaccination induces a relatively greater Th2 cell response that can cure and prevent infection in H. felis/ mice models. 128,129,135,139 Thus, with the discovery of the appropriate formulation and routes of administration, it is possible that vaccination could trigger an immune response that differs substantially from that induced by natural infection with H. pylori. Undoubtedly, the continuous efforts of laboratories around the world to develop a vaccine and therapeutic approaches may soon bring an end to the long evolutionary relationship between humankind and Helicobacter pylori.…”
Section: Vaccination Development For Clinical Use and Future Of The Hmentioning
confidence: 99%